Completion of adjuvant therapy in patients with resected pancreatic cancer. Issue 2 (February 2020) - DePeralta, Danielle K.; Ogami, Takuya; Zhou, Jun-Min; Schell, Michael J.; Powers, Benjamin D.; Hodul, Pamela J.; Malafa, Mokenge P.; Fleming, Jason B.
Abstract: Background: Adjuvant chemotherapy is the standard of care for resected pancreatic ductal adenocarcinoma (PDAC). It is estimated that only 40–80% eligible patients initiate intended adjuvant chemotherapy. Completion rates are largely unknown. Methods: A retrospective analysis of outcomes of patients with resected PDAC over an 8-year period at H. Lee Moffitt Cancer Center (MCC) was performed. Results: From a total of 309 patients, 299 were included for further analysis. 242 (81%) initiated adjuvant therapy (AT) and 195 (65%) completed the intended course. The median time-to-initiation of AT was 53 days (7.6 weeks). The most common reasons for early discontinuation of AT (n = 47) were toxicity (n = 29), disease recurrence (n = 9), patient decision (n = 4), unrelated comorbidities (n = 3), and death (n = 1). Completion of AT was an independent predictor of overall survival (OS) and recurrence-free survival (RFS) on multivariable analysis (OS: HR 0.41, CI 0.27–0.61, p < 0.001; RFS: HR 0.52, CI 0.36–0.76, p < 0.001). Factors associated with early termination of AT were vascular resection (OR 0.29, CI 0.13–0.67, p = 0.004) and administration of AT with local oncologist as opposed to MCC (OR 0.41, CI 0.21–0.82, p = 0.010). Conclusion: Completion of AT is associated with improved survival in patients with resected PDAC. Factors associated with an inability to complete AT include vascular resection and administration of AT with local care team in the patient's community.